5(u-1)-2=-5(-4u+2)-9u

Since u is on the right side of the equation, switch the sides so it is on the left side of the equation.

-5(-4u+2)-9u=5(u-1)-2

Simplify each term.

Apply the distributive property.

-5(-4u)-5⋅2-9u=5(u-1)-2

Multiply -4 by -5.

20u-5⋅2-9u=5(u-1)-2

Multiply -5 by 2.

20u-10-9u=5(u-1)-2

20u-10-9u=5(u-1)-2

Subtract 9u from 20u.

11u-10=5(u-1)-2

11u-10=5(u-1)-2

Simplify each term.

Apply the distributive property.

11u-10=5u+5⋅-1-2

Multiply 5 by -1.

11u-10=5u-5-2

11u-10=5u-5-2

Subtract 2 from -5.

11u-10=5u-7

11u-10=5u-7

Subtract 5u from both sides of the equation.

11u-10-5u=-7

Subtract 5u from 11u.

6u-10=-7

6u-10=-7

Add 10 to both sides of the equation.

6u=-7+10

Add -7 and 10.

6u=3

6u=3

Divide each term in 6u=3 by 6.

6u6=36

Cancel the common factor of 6.

Cancel the common factor.

6u6=36

Divide u by 1.

u=36

u=36

Cancel the common factor of 3 and 6.

Factor 3 out of 3.

u=3(1)6

Cancel the common factors.

Factor 3 out of 6.

u=3⋅13⋅2

Cancel the common factor.

u=3⋅13⋅2

Rewrite the expression.

u=12

u=12

u=12

u=12

The result can be shown in multiple forms.

Exact Form:

u=12

Decimal Form:

u=0.5

Solve for u 5(u-1)-2=-5(-4u+2)-9u